1985
DOI: 10.1136/bmj.290.6482.1611
|View full text |Cite
|
Sign up to set email alerts
|

Domiciliary nebulisers in asthma: a district survey.

Abstract: Fifty three patients who were found to be using a home nebuliser for asthma completed a questionnaire. The results showed some confusion about the criteria for recommending whether a patient should buy a nebuliser and for its correct use. Twelve patients had not received any instruction on the use of their nebuliser, and only 11 of those old enough used a peak flow meter in conjunction with it. Eight patients aged 7-15 were using inhaled sympathomimetic aerosols only at the time of buying a nebuliser as compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 7 publications
(4 reference statements)
1
4
0
Order By: Relevance
“…Despite the widespread lack of instructions on use and, above all, maintenance of home nebulizers from healthcare workers, the patients never complained. This finding has been seen in a previous study [12] and it has been shown that confidence in nebulizer use does not automatically mean that the practices were appropriate [5]. Interestingly, when healthcare workers provided more information on nebulizer use and maintenance, patients took better care of these practices.…”
Section: Discussionsupporting
confidence: 65%
“…Despite the widespread lack of instructions on use and, above all, maintenance of home nebulizers from healthcare workers, the patients never complained. This finding has been seen in a previous study [12] and it has been shown that confidence in nebulizer use does not automatically mean that the practices were appropriate [5]. Interestingly, when healthcare workers provided more information on nebulizer use and maintenance, patients took better care of these practices.…”
Section: Discussionsupporting
confidence: 65%
“…It may occur in a quarter ofdiabetic outpatients,2 and plasma magnesium concentration varies inversely with blood glucose concentration in these patients. 3 During the treatment of diabetic ketoacidosis the plasma magnesium concentration may fall severely such that magnesium supplements are required.4 Although our patient was not ketotic, her diabetes was undoubtedly poorly controlled. In addition, she was taking frusemide, and diuretics are known to induce hypomagnesaemia.5 This combination may have accounted for the severity of her hypomagnesaemia.…”
Section: Commentmentioning
confidence: 79%
“…The device was evaluated by comparing its readings with those obtained with a Wright peak flow meter. Altogether 101 children (65 boys, 36 girls) aged [3][4][5][6][7][8][9][10][11][12] were instructed to blow three times into a standard Wright peak flow meter and three times through the whistle. The peak flow meter was used first so that the whistle could be preset to a point where theehild would be likely to sound it.…”
Section: Subjects Methods and Resultsmentioning
confidence: 99%